When the Court Decisions Encourage Deforestation in Indonesia - Rosariani, Putu Eka; Widiatedja, I Gusti Ngurah Parikesit; Qadam Shah, Muhammad (Indonesian Journal of Law and Society, 2023)
The abstract presents a critical analysis of the role played by court decisions in the prevention of deforestation. Over the past few decades, Indonesia has witnessed extensive deforestation, primarily due to the expansion of oil palm and agriculture. This has had a significant impact on Bali's tourism industry, which heavily relies on this sector for development. The Tahura Mangrove Forest Project serves as an example of a tourism venture that has resulted in damage to the forested area. Despite the prohibition of commercial projects on protected land, the government issued a utilization permit for the construction of guest houses. Rather than effectively curbing deforestation, this study demonstrates how controversial court decisions have actually encouraged it. The courts' assertion that public interest groups lacked standing to challenge violations of forestry laws, which could potentially cause environmental harm, was based on the argument that the damage was only a possibility during the planning stage and could not be accurately quantified. This paper identifies three factors contributing to the judges' adoption of a narrow standing test: their limited judicial competence, reliance on the Supreme Court's existence, and corruption.